Differences between Mothers' and Fathers' Ratings of Family Functioning with the Family Assessment Device: The Validity of Combined Parent Scores - Cooke, D.; Marais, I.; Cavanagh, R.; Kendall, Garth; Priddis, L. (SAGE Publications Inc., 2015)
The psychometric properties of the General Functioning subscale of the McMaster Family Assessment Device were examined using the Rasch Model (N = 237 couples). Mothers' and fathers' ratings of the General Functioning subscale of the McMaster Family Assessment Device are recommended, provided these are analyzed separately. More than a quarter of couples differed significantly in their ratings.